Probe data mapping using contact information (2023)
A method of mapping includes receiving inputs measured by a probe at respective locations inside a body cavity of a subject. At each of the respective locations, a respective contact quality between the probe and a tissue in the body cavity is measured. The inputs for which the respective contact quality is outside a defined range are rejected, and a map of the body cavity is created using the inputs that are not rejected.